2013
DOI: 10.1016/j.jnucmat.2013.07.071
|View full text |Cite
|
Sign up to set email alerts
|

A systematic study of radiation-induced segregation in ferritic–martensitic alloys

Abstract: A systematic approach to measuring radiation-induced segregation (RIS) was used on four ferritic-martensitic (F-M) alloys: T91, HCM12A, HT9, and a Fe-9Cr model alloy, irradiated with 2.0 MeV protons over a range of doses (1-10 dpa) and temperatures (300-700°C). The experimental conditions are established so as to isolate the dependence of RIS on the experimental parameters: temperature, dose and bulk composition. RIS is measured at prior austenite grain boundaries (PAGBs) using the STEM-EDS technique. Chromium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
57
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 27 publications
11
57
0
2
Order By: Relevance
“…More recently, ab initio calculations have suggested that Cr RIS or RID is a competition between interstitial and vacancy mechanisms and depends on the relative amplitude between both [21][22][23]. This argument was used later by Wharry et al to explain their field emission gun/scanning transmission electron microscopy (FEG/STEM) X-ray measurements in a set of F-M alloys [24]. They showed that RIS would occur at lower temperatures when Cr is dragged by interstitial flux, while RID would occur at higher temperatures when Cr is dragged by vacancy flux.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, ab initio calculations have suggested that Cr RIS or RID is a competition between interstitial and vacancy mechanisms and depends on the relative amplitude between both [21][22][23]. This argument was used later by Wharry et al to explain their field emission gun/scanning transmission electron microscopy (FEG/STEM) X-ray measurements in a set of F-M alloys [24]. They showed that RIS would occur at lower temperatures when Cr is dragged by interstitial flux, while RID would occur at higher temperatures when Cr is dragged by vacancy flux.…”
Section: Introductionmentioning
confidence: 99%
“…Для цього стану, як можна показати, градієнт концентрації компонента А пов'язаний з градієнтом концентрації вакансій таким співвідношенням [13]:…”
Section: Ai Iunclassified
“…Експерименти показують [4][5][6][7][8][9][10][11][12][13], що під час опромінення сплаву при підвищених температурах (0.3 -0.5 T пл. ) [14] відбувається просторовий перерозподіл компонентів даного сплаву.…”
unclassified
“…Together, these two irradiations illustrate that phenomena such as intermixing at metal-oxide interfaces is very sensitive to the irradiation conditions. In particular, it has been established that temperature plays a very important role on radiation-induced segregation at these types of interfaces [29].…”
Section: Irradiated Undoped Fe/tio 2 Interfacesmentioning
confidence: 99%